Pengembangan Modul Pembelajaran Matematika Berbasis Etnomatematika Menggunakan Metode Inkuiri - Mardiah, Siti; widyastuti, Rany; Rinaldi, Achi (Desimal: Jurnal Matematika, 2018)
This research entitled Development of Mathematics Based Module of Ethnomathematics using Inkuiri method. This study aims to find out how the development of mathematics learning module based on ethnomathematics using inquiry method, and to know the teacher and student response to the development of mathematics learning module based on ethnomathematics using inquiry method. This research method is Research and Development (R&D) using 4D model. Based on the results of the validation of stage 1 by the material experts obtained a cumulative average of 65.36% with the criteria of "good enough" which means that there is an improvement of some aspects contained in the module. After performing a series of revisions, the average score of cumulative of 84.02% validation with "good" criterion was obtained, so there is no revision of the module. The average score of cumulative validation of stage 1 by a media expert is 60% with a "good enough" code which means that it needs to be revised in some parts of the module. In the second stage of validation, the average cultivation is 86.66% with "very good" criteria so that the module is valid and ready for a field trial. From the results of research teacher response to the module obtained an average of 86.15% with the criteria "very interesting". In the small group trial, the average of 85% was obtained with interesting criteria and large group trial obtained an average of 87.28% with very interesting criteria so that the module is feasible and ready to be used as teaching materials.